Aprendizagem Baseada em Projetos na formação de alunos de um curso de Licenciatura em Letras: estudo de caso em uma Instituição de Ensino Salesiana - Oliveira, Neide Aparecida Arruda de (2019)
This PhD thesis studies the active methodology Project-Based Learning (PBL). Its focus is the training of undergraduate students who study Letters verifying in the process of teaching and learning their preparation for the digital age, the so-called Era of Knowledge. The question in question refers to: how does the undergraduate student's training in a Salesian HEI take place through the active teaching method "Project-Based Learning"? From this problematization, the objectives of the research are: to make a review of literature on Project-Based Learning; to do a literature review on Project-Based Learning in higher education in the Literature course; to analyze the active method of teaching "Project Based Learning" of the course of Letters of a Salesian HEI through the Folhetim Lorenianas project under the eyes of students and those of the community. The methodology is based on qualitative research (Yin, 2015) for case study. The data collection was carried out through a questionnaire composed of 10 open questions and was presented to the students who are in the second, third and fourth years of the Portuguese / English Literature that participated in the Folhetim Lorenianas project, totaling fifty-nine students and to five members of the local community representing the Academy of Letters of Lorena (scope of the Folhetim Loreninas). The categorization and analysis of the data was done through the content analysis of Bardin (2011). The results showed that ABP develops the skills of the 21st century, but it is a great challenge in view of teacher training. There is a need to invest in this training so that the professionals who are working on the training of new teachers are updated both pedagogically and technologically. This thesis fills a gap regarding the training of teachers in the course of Letters using the active methodology Project-Based Learning